Digital vaulted territories: Development of a cross-tool platform for vaults’ knowledge - Pacheco, M. B.; Falcão, A. P.; Gomes, M. da G.; Volzone, R.; Folgado, M. P.; Costa, S. (Revista de História da Arte, 2025)
Within the scope of the Vaulted South Project, an open-source platform was implemented using Omeka-S software to store and interconnect digital data and enable research and dissemination – based on the FAIR principles (Findable, Accessible, Interoperable and Reusable) – of knowledge of vernacular vaulted buildings in Southern Portugal. The corpus was generated by crossing several methodologies and interrelated heterogeneous data on vaults, covering digital transcription, digital photography, laser measurement, terrestrial laser scanning, parametric BIM modelling, and non-destructive inspection techniques such as infrared thermography. This article presents the structure of the database and reflects on the operability of the exploratory methodological approach developed in the project, which encompasses data from several fieldwork campaigns, covering a specific geographical area. It reveals the importance of using innovative methods to achieve accurate data in a more efficient and less intrusive way when dealing with unstudied current buildings. Combining traditional and digital methods of surveyance, data acquisition, data management, communication and scientific dissemination, which are often employed separately in the fields of Architecture, History of Art and Engineering, the Vaulted South Project provided opportunities to bring these scientific fields together as a common field to the History of Architecture and the Digital Humanities.